Взаимосвязь вариабельности и уровня гликемии со структурно-функциональными показателями сердца у больных хронической сердечной недостаточностью на фоне сахарного диабета 2 типа - Сыволап, В. Д.; Капшитарь, Н. И.; Сиволап, Віктор Денисович; Капшитар, Наталія Ігорівна (My University, 2016)
Проанализированы результаты эхокардиографии пациентов с хронической сердечной недостаточностью ишемического генеза на фоне сахарного диабета 2 типа в зависимости от степени вариабельности гликемического профиля и среднего уровня гликемии. Выявлено отрицательное влияние высокой вариабельности гликемии на систолическую и диастолическую функцию сердца, размер левого предсердия, и отсутствие достоверного влияния на кардиогемодинамику среднего уровня гликемии An important contribution in the development of diabetes mellitus (DM) complications makes not only the chronic hyperglycemia but also the intense diurnal glycemia variability (GV). The aim of research was to assess systolic and diastolic heart functions in patients with chronic heart failure (CHF) of ischemic genesis on the background of DM type 2 depending on GV profile and the mean level of glycemia during the last 3 month. Methods: There were examined 65 patients who were divided into groups twice on the different categoric indicators. The first indicator – an intensity of glycemia profile (GP) variability, the second – the mean calculated level of glucose concentration in patients during the last 3 month. All patients underwent dopplerechocardiography, the standard declination and the coefficient of GP variations were calculated. An assessment of reliability of the results of statistic study was carried out by nonparametric method. Results: in patients with the high GP variability was detected the reliably greater size of the left atrium, decrease of the left ventricle output fraction, tendency to the transition of diastolic dysfunction from the I type to the II one comparing with the group with low GP variability. There was not revealed any reliable difference between groups or correlative connection of the mean level of glycemia with parameters that characterize contractility and diastolic myocardium function. Conclusions: There was revealed the negative influence of the high glycemia variability on systolic and diastolic heart functions, left atrium size and there was not revealed any reliable influence of the mean level of glycemia on cardiohemodynamics.
The relationship of diurnal variability and level of glycemia with structural and functional parameters of heart in patients with chronic heart failure and diabetes mellitus type 2
Keywords: хроническая сердечная недостаточность; сахарный диабет; систолическая и диастолическая функция сердца; вариабельность гликемического профиля; chronic heart failure; diabetes mellitus; systolic and diastolic heart functions; glycemia profile variability